Potencies of vitamin D analogs, 1α‐hydroxyvitamin D3, 1α‐hydroxyvitamin D2 and 25‐hydroxyvitamin D3, in lowering cholesterol in hypercholesterolemic mice in vivo. (25th April 2018) - Quach, Holly P.; Dzekic, Tamara; Bukuroshi, Paola; Pang, K. Sandy
Abstract: Vitamin D3 and the synthetic vitamin D analogs, 1α‐hydroxyvitamin D3 [1α(OH)D3 ], 1α‐hydroxyvitamin D2 [1α(OH)D2 ] and 25‐hydroxyvitamin D3 [25(OH)D3 ] were appraised for their vitamin D receptor (VDR) associated‐potencies as cholesterol lowering agents in mice in vivo . These precursors are activated in vivo : 1α(OH)D3 and 1α(OH)D2 are transformed by liver CYP2R1 and CYP27A1 to active VDR ligands, 1α, 25‐dihydroxyvitamin D3 [1, 25(OH)2 D3 ] and 1α, 25‐dihydroxyvitamin D2 [1, 25(OH)2 D2 ], respectively. 1α(OH)D2 may also be activated by CYP24A1 to 1α, 24‐dihydroxyvitamin D2 [1, 24(OH)2 D2 ], another active VDR ligand. 25(OH)D3, the metabolite formed via CYP2R1 and or CYP27A1 in liver from vitamin D3, is activated by CYP27B1 in the kidney to 1, 25(OH)2 D3 . In C57BL/6 mice fed the high fat/high cholesterol Western diet for 3 weeks, vitamin D analogs were administered every other day intraperitoneally during the last week of the diet. The rank order for cholesterol lowering, achieved via mouse liver small heterodimer partner ( Shp ) inhibition and increased cholesterol 7α‐hydroxylase ( Cyp7a1 ) expression, was: 1.75 nmol/kg 1α(OH)D3  > 1248 nmol/kg 25(OH)D3 (dose ratio of 0.0014) > > 1625 nmol/kg vitamin D3 . Except for 1.21 nmol/kg 1α(OH)D2 that failed to lower liver and plasma cholesterol contents, a significant negative correlation was observed between the liver concentration of 1, 25(OH)2 D3 formed from the precursors and liver cholesterol levels. The composite results show that vitamin D analogs 1α(OH)D3 and 25(OH)D3 exhibit cholesterol lowering properties upon activation to 1, 25(OH)2 D3 : 1α(OH)D3 is rapidly activated by liver enzymes and 25(OH)D3 is slowly activated by renal Cyp27b1 in mouse.